1996
DOI: 10.1007/s004240050233
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of calcium release by calcium inside the sarcoplasmic reticulum in ventricular myocytes

Abstract: To study the effects of changes in sarcoplasmic reticulum (SR) intraluminal Ca2+ on the Ca2+ release mechanism, we correlated the activity of single cardiac ryanodine receptor (RyR) channels, monitored in planar bilayers, with the properties of spontaneous elementary Ca2+ release events (sparks) in intact ventricular myocytes, monitored by scanning confocal microfluorimetry. Under both normal conditions and Ca2+ overload, induced by elevation of extracellular [Ca2+], Ca2+ sparks represented single populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
200
2
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(228 citation statements)
references
References 28 publications
24
200
2
2
Order By: Relevance
“…This could be a direct consequence of the increased SR Ca 2ϩ load. It has been shown that intraluminal Ca 2ϩ regulatory mechanisms cause a potentiation of SR Ca 2ϩ release in cardiac cells in response to increases in SR Ca 2ϩ load (1,5,24 SERCA1a hearts in vivo show moderately increased cardiac contractility and blunted response to Dob. In vivo baseline contractility in TG hearts was moderately increased, whereas relaxation parameters, in contrast to the observations in the isolated hearts, were unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a direct consequence of the increased SR Ca 2ϩ load. It has been shown that intraluminal Ca 2ϩ regulatory mechanisms cause a potentiation of SR Ca 2ϩ release in cardiac cells in response to increases in SR Ca 2ϩ load (1,5,24 SERCA1a hearts in vivo show moderately increased cardiac contractility and blunted response to Dob. In vivo baseline contractility in TG hearts was moderately increased, whereas relaxation parameters, in contrast to the observations in the isolated hearts, were unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation may be inactivation of ryanodine receptor channels by Ca¥ from the cytoplasmic side, which has been observed in skinned myocardial fibres (Fabiato, 1985) and with ryanodine receptor channels incorporated into lipid bilayers (Laver, Roden, Ahern, Eager, Junankar & Dulhunty, 1995;Sitsapesan, Montgomery & Williams, 1995;Shiefer, Meissner & Isenberg, 1995). Ca¥ sparks are also reported to be influenced by intraluminal Ca¥ of the SR (Lukyanenko, Gyorke & Gyorke, 1996). Translocation of SR Ca¥ to a releasable pool (Wier & Yue, 1985) within the Ca¥ release unit at each Z-line might also explain the refractory period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, spontaneous Ca 2ϩ sparks were observed after 64% reduction in SR Ca 2ϩ loading (41). However, the data do not exclude the possibility that the partial SR Ca 2ϩ depletion may play a contributing role in terminating Ca 2ϩ release by altering RyR activities (42,43), and reducing the gain of CICR (24).…”
Section: ؉mentioning
confidence: 92%